A Simple Quantitative Assay for Measuring β‐Galactosidase Activity Using X‐Gal in Yeast‐Based Interaction Analyses. Issue 5 (14th May 2022) - Trimborn, Laura; Hoecker, Ute; Ponnu, Jathish
Abstract: Yeast‐based interaction assays to determine protein‐protein and protein‐nucleic acid interactions commonly rely on the reconstitution of chimeric transcription factors that activate the expression of target reporter genes. The enzyme β‐galactosidase (β‐gal), coded by the LacZ gene of Escherichia coli, is a widely used reporter in yeast systems, and its expression is commonly assessed by evaluating its activity. X‐gal (5‐bromo‐4‐chloro‐3‐indolyl‐β‐d ‐galactopyranoside) is an inexpensive and sensitive substrate of β‐gal, whose hydrolysis results in an intensely blue colored and easily detectable end product, 5, 5′‐dibromo‐4, 4′‐dichloro‐indigo. The insoluble nature of this end product, however, makes X‐gal‐based assays unsuitable for direct spectrophotometric absorbance quantification. As such, the use of X‐gal is mostly restricted to solid‐support approaches, such as colony lift or agar plate assays, which often only provide a qualitative readout. In this article, we describe a quantitative solid‐phase X‐gal assay to measure protein‐protein interaction strength in yeast cells using a simple and low‐cost experimental setup. We have optimized multiple aspects of the assay, namely sample preparation, reaction time, and quantification method, for speed and consistency. By integrating the use of a freely available ImageJ‐based plugin, we have further standardized the assay for reliability and reproducibility. This improved quantitative X‐gal assay can be performed in a standard molecular biology lab without the need for any specialized equipment other than an inexpensive and widely accessible smartphone camera. To exemplify the protocol, we provide detailed step‐by‐step instructions to perform a quantitative X‐gal assay to assess the interaction between two Arabidopsis thaliana proteins, SUPPRESSOR OF PHYA‐105 1 (SPA1) and PRODUCTION OF ANTHOCYANIN PIGMENT 2 (PAP2). To demonstrate the sensitivity of our assay in detecting weaker interactions, we also compare the results with a liquid‐phase assay that uses ONPG ( ortho ‐nitrophenyl‐β‐galactopyranoside) as a substrate for β‐gal. The quantitative X‐gal assay described here can easily be adapted for high‐throughout interaction studies and protein domain mapping, even in yeast strains with low levels of LacZ expression. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Preparation of competent yeast cells and transformation Alternate Protocol 1 : In‐house preparation of yeast competent cells for use in lithium acetate (LiAc)–mediated yeast transformation Support Protocol : Long‐term storage and revival of frozen yeast strain stocks Basic Protocol 2 : Measuring β‐galactosidase activity via the quantitative X‐gal assay Alternate Protocol 2 : Quantification of interaction strength using liquid ONPG assay